A novel inherited SCN1A mutation associated with GEFS+ in benign and encephalopathic epilepsy. (June 2017) - Gauthier, Angela C.; Manganas, Louis N.; Mattson, Richard H.
Highlights: SCN1A mutations may cause generalized epilepsy with febrile seizures plus (GEFS+). A novel SCN1A mutation was found in an 8-year-old boy with GEFS+. The boy has intractable afebrile generalized seizures and cognitive decline. The father has the same mutation, but he only had childhood simple febrile seizures. The severity of SCN1A mutations depends on many factors still under investigation. Abstract: Generalized epilepsy with febrile seizures plus (GEFS+) is an autosomal dominant condition often caused by mutations in SCN1A that usually first manifests as childhood simple febrile seizures but may progress to a variety of afebrile generalized seizure types. Here, we describe the case of an 8-year-old boy with a novel SCN1A mutation who developed febrile seizures at 10 months of age which eventually advanced to frequent afebrile tonic-clonic seizures. His condition was unresponsive to several antiepileptic drugs and the ketogenic diet, and he experienced gradual cognitive decline. The patient's father carries the same novel mutation, but he only experienced childhood simple febrile seizures. SCN1A mutations display incomplete penetrance and variable expressivity, and the resulting severity may depend on the location and type of mutation, whether the mutation was spontaneous or inherited, and the effect of modifying alleles. The identification of novel pathogenic SCN1A mutations may eventually advance therapeutic development and prognostic capabilities.